STI epidemics in the Indian Ocean region: can the phase be assessed?. (1st April 2002) - Matteelli, A; Pizzocolo, C; Abdou Bakar, H; Toyb, M; Pyndiah, N; Udonwa, N E; Gedeon, A G; Farina, C; Caligaris, S; Castelli, F; Carosi, G
Abstract : The Indian Ocean provides a unique opportunity to curb the HIV epidemic in its nascent phase through strengthening STI control programmes. Making effective and appropriate health services available should be regarded as the first priority for STI control in the region and, whenever possible, core groups should be identified and targeted to interrupt transmission within such networks.